2020
DOI: 10.3389/fpsyg.2020.01240
|View full text |Cite
|
Sign up to set email alerts
|

Moved by Observing the Love of Others: Kama Muta Evoked Through Media Fosters Humanization of Out-Groups

Abstract: People often view out-groups as less human than their in-group. Some media video content is heart-warming and leaves one feeling touched or moved . Recent research indicates that this reflects a positive social emotion, kama muta , which is evoked by a sudden increase in interpersonal closeness, specifically by the relational model of communal sharing. Because forming strong, close, and communal bonds exemplifies valued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…In those studies, viewers experienced "elevation," which is a sense of relaxation while being uplifted, usually accompanied by physical sensations such as warmth (86). These and other studies showed that viewers felt a greater sense of feeling connected to others, including to members of other racial or cultural groups (84) and decreases in dehumanization of others (87).…”
Section: Use Of Positive Media In Waiting Roomsmentioning
confidence: 90%
“…In those studies, viewers experienced "elevation," which is a sense of relaxation while being uplifted, usually accompanied by physical sensations such as warmth (86). These and other studies showed that viewers felt a greater sense of feeling connected to others, including to members of other racial or cultural groups (84) and decreases in dehumanization of others (87).…”
Section: Use Of Positive Media In Waiting Roomsmentioning
confidence: 90%
“…Future studies should explore the possibility of kama muta being able to decrease stress and if so, by what mechanism. Past studies have found evidence that kama muta increases social connectedness to other individuals, which could be an important mechanism (Blomster Lyshol et al, 2020;Zickfeld, 2015;Zickfeld, Schubert, Seibt, Blomster, et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%
“…In addition, kama muta is assumed to motivate communal action such as hugging, taking care, or helping others and it is often labeled with terms such as moved, touched, or heartwarming in English vernacular (Fiske et al, 2019). The kama muta framework has been supported by several empirical studies in various cultures (Blomster Lyshol, Seibt, & Thomsen, 2020;Seibt et al, 2018;Steinnes, Blomster, Seibt, Zickfeld, & Fiske, 2019;Zickfeld, Schubert, Seibt, Blomster, et al, 2019;.…”
Section: Kama Muta-being Moved By Lovementioning
confidence: 99%
“…Kama muta is mainly studied in response to narratives in online videos (Schubert et al, 2018;Zickfeld et al, 2019) or in response to pictures and videos showing cute animals (Steinnes, Blomster, Seibt, Zickfeld, & Fiske, 2019). Situations that elicit kama muta can contribute to humanizing out-groups (Blomster Lyshol, Thomsen, & Seibt, 2020). These feelings and consequences of kama muta exhibit considerable overlap with the feelings and consequences of moral elevation and awe.…”
Section: Kama Mutamentioning
confidence: 99%